2011
DOI: 10.1002/ps.2094
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory assays of select candidate insecticides for control of Dendroctonus ponderosae

Abstract: BACKGROUND: The mountain pine beetle, Dendroctonus ponderosae Hopkins (Coleoptera: Curculionidae, Scolytinae), is the most destructive bark beetle in western North America. Dendroctonus ponderosae can be prevented from successfully colonizing and killing individual trees by ground-based sprays of insecticides applied directly to the tree bole. However, the future availability of several active ingredients, including carbaryl which is most commonly used in the western United States, is uncertain. Two novel inse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 22 publications
0
23
0
Order By: Relevance
“…This was unexpected as fall treatments were subjected to an additional nine months of degradation compared to spring treatments (i.e., from mid-September 2009 to mid-June 2010) before being challenged by D. ponderosae, which we thought would be sufficient to limit efficacy to one field season. While the amount of carbaryl on pine bark necessary to impart tree protection from D. ponderosae is unknown, Fettig et al (2011) found no significant differences in the survival probability of D. ponderosae in filter paper assays between 20,000 mg g À1 carbaryl (i.e., 2% a.i.) and lesser concentrations until reaching 20 mg g À1 (i.e., via 10-fold serial dilutions).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…This was unexpected as fall treatments were subjected to an additional nine months of degradation compared to spring treatments (i.e., from mid-September 2009 to mid-June 2010) before being challenged by D. ponderosae, which we thought would be sufficient to limit efficacy to one field season. While the amount of carbaryl on pine bark necessary to impart tree protection from D. ponderosae is unknown, Fettig et al (2011) found no significant differences in the survival probability of D. ponderosae in filter paper assays between 20,000 mg g À1 carbaryl (i.e., 2% a.i.) and lesser concentrations until reaching 20 mg g À1 (i.e., via 10-fold serial dilutions).…”
Section: Discussionmentioning
confidence: 85%
“…In topical assays, significantly higher survival probabilities were observed for concentrations 2000 mg g À1 of carbaryl, suggesting levels below 2000 mg g À1 may be less effective for tree protection. Mean LC 50 values for D. ponderosae were 132.9 mg g À1 at 12 h (Fettig et al, 2011). Page et al (1985) reported residues collected from P. contorta bark sprayed with carbaryl in Colorado were 890 mg g…”
Section: Discussionmentioning
confidence: 99%
“…/liter, in chemical control of insects (Lepidoptera) caterpillar, beetles (Coleoptera), aphids or shield bugs from the family Pentatomidae (Hemiptera) and other pests [11]- [14]. Is highly potent and efficacious against a wide range of economically important Lepidoptera species, and is also effectively in control species from other orders such as Diptera and Isoptera.…”
Section: Resultsmentioning
confidence: 99%
“…DuPont de Nemours and Company, Inc. with a novel mode of action. It is a second generation RyR (action only by activating ryanodine receptors) insecticide with a similar mode of action to Rynaxypyr TM (chlorantraniliprole) [11]. Cyazypyr TM activates ryanodine receptors via stimulation of the release of calcium stores from the sarcoplasmic reticulum of muscle cells (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Cyantraniliprole is a second generation anthranilic diamide insecticide, and it shares a similar mode of action with chlorantraniliprole. It is a novel insecticide that is showing promise as a control agent against agricultural and horticultural pests (Fettig et al 2011, Hardke et al 2011, Jacobson and Kennedy 2011, Li et al 2011), but it is rarely used for termite management. In the current study, we found that cyantraniliprole is toxic to C. gestroi.…”
Section: Discussionmentioning
confidence: 97%